2018
DOI: 10.1016/j.ecoenv.2017.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nitrogen-polycyclic aromatic hydrocarbons on phenanthrene and benzo[a]pyrene mineralisation in soil

Abstract: When aromatic hydrocarbons are present in contaminated soils, they often occur in mixtures. The impact of four different (3-ring) nitrogen-containing polycyclic aromatic hydrocarbons (N-PAHs) on C-phenanthrene andC-benzo[a]pyrene (B[a]P) mineralisation in soil was investigated over a 90 d incubation period. The results revealed that both C-phenanthrene andC-benzo[a]pyrene showed no significant mineralisation in soils amended with 10mgkg and 100mgkg N-PAHs (p>0.05). However, increases in lag-phases and decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Despite the widespread uses of N-PAHs, and previous N-PAHs studies in literature (Anyanwu and Semple, 2015a;2015b;2016a;Anyanwu et al, 2017), there has not been information of their impacts on microbial utilization of 14 C-glucose and/or synthesis of cell biomass in soil. Functionally, microbes can act as relevant indicators of environmental pollution; as a result, there is great need to assess the impact of N-PAHs on soil microbial metabolism and biosynthesis of cell biomass.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the widespread uses of N-PAHs, and previous N-PAHs studies in literature (Anyanwu and Semple, 2015a;2015b;2016a;Anyanwu et al, 2017), there has not been information of their impacts on microbial utilization of 14 C-glucose and/or synthesis of cell biomass in soil. Functionally, microbes can act as relevant indicators of environmental pollution; as a result, there is great need to assess the impact of N-PAHs on soil microbial metabolism and biosynthesis of cell biomass.…”
Section: Introductionmentioning
confidence: 99%
“…It played an important role in its toxic effects both on plants, invertebrates, and microorganisms. Results found that there was no significant mineralization of B(a)P in soils in the rates and extents even over a 90 days incubation period (Anyanwu et al, 2018), and existed the remobilization risk of non‐extractable residues (NERs depending on the aging, spiked concentration, and soil properties (Luo et al, 2012; Umeh et al, 2018). We sampled and purchased soil samples with some uncertainty, and they can represent the complicated real environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Benzo(a)pyrene [B(a)P] with five fused benzene rings is a ubiquitous soil pollutant, which has been regarded as a representative indicator of polycyclic aromatic hydrocarbons, due to its persistence, biological toxicity, carcinogenicity, mutagenicity, and potential for bioaccumulation (Du et al, 2020; IARC, 2012; Lemieux et al, 2015). Reports showed that there exists no significant mineralization of B(a)P in soils (in the rates and extent) even over a 90 d incubation period (Anyanwu et al, 2018). Although non‐extractable residues (NER) could be formed after 33 d of aging, the remobilization risks still exist depending on the aging time, spiked concentrations, and soil properties (Luo et al, 2012; Umeh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil contaminated with polynuclear aromatic hydrocarbons (PAHs) is a major environmental problem worldwide, mainly caused by the incomplete combustion of organic macromolecule substances generally concerning industrial and urban activities 1 . PAHs such as phenanthrene (PHE) and pyrene (PYR) have become the most ubiquitous environmental pollutants 2 . Due to highly mutagenic and carcinogenic properties and being commonly found in soil at high concentrations in many countries, PHE and PYR soil contamination has attracted particular attention 3 .…”
Section: Introductionmentioning
confidence: 99%